Coping strategies and their sociodemographic correlates: an analysis of Ecuatorian university student behavior - González-González, Dalila M.; Guerrero-Vásquez, Luis F.; Quito-Calle, Jessica V. (Frontiers in Education, 2025)
IntroductionUniversity life presents numerous challenges that can affect students' emotional well-being and academic performance. Understanding how students cope with these challenges is essential for developing effective support strategies.MethodsThis study employed a quantitative approach with a cross-sectional descriptive-correlational design. A total of 464 university students from various academic disciplines at a higher education institution in Azogues, Ecuador, participated. Coping strategies were assessed using the Brief COPE inventory, and sociodemographic data were collected through an online form. Data analysis was conducted using SPSS software.ResultsFemale students most frequently used emotional support, instrumental support, and religion as coping strategies. In contrast, male students tended to rely more on substance use and positive reinterpretation. Statistically significant differences were also observed in the use of humor and according to academic level.DiscussionThese findings underscore the relevance of sociodemographic factors in shaping coping strategies among university students. The study provides a foundation for targeted interventions that promote adaptive coping and enhance student well-being in higher education contexts.